2017
DOI: 10.3762/bjnano.8.59
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and surface alloying of gradient nanostructured metals

Abstract: Gradient nanostructures (GNSs) have been optimized in recent years for desired performance. The diffusion behavior in GNS metals is crucial for understanding the diffusion mechanism and relative characteristics of different interfaces that provide fundamental understanding for advancing the traditional surface alloying processes. In this paper, atomic diffusion, reactive diffusion, and surface alloying processes are reviewed for various metals with a preformed GNS surface layer. We emphasize the promoted atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…It is noticeable that the effective interfacial diffusivity in DPD Ni is by more than 2 orders of magnitude higher than the GB self-diffusion rate in coarse-grained Ni. Significantly enhanced interfacial diffusion kinetics have previously been observed in nanostructured materials produced by different SPD routes [5,10,11,18,25]. This was attributed to a deformation-modified state of GBs, which accumulate a large number of extrinsic dislocations and possess higher free energy in comparison with conventional GBs in coarse-grained samples.…”
Section: Resultsmentioning
confidence: 85%
“…It is noticeable that the effective interfacial diffusivity in DPD Ni is by more than 2 orders of magnitude higher than the GB self-diffusion rate in coarse-grained Ni. Significantly enhanced interfacial diffusion kinetics have previously been observed in nanostructured materials produced by different SPD routes [5,10,11,18,25]. This was attributed to a deformation-modified state of GBs, which accumulate a large number of extrinsic dislocations and possess higher free energy in comparison with conventional GBs in coarse-grained samples.…”
Section: Resultsmentioning
confidence: 85%
“…Since there is no interface separating the surface layer and the substrate, the problem of poor interface bonding between the nanostructured surface layer and the substrate, usually caused by traditional coating techniques, is easily solved ( Nana & Ning, 2018 ; Du et al, 2019 ). In addition, SMAT materials have the advantages of high strength, high hardness, high diffusion rate and high chemical reactivity, and their wear resistance and fatigue resistance are also significantly improved ( Nowak, Serafin & Wierzba, 2019 ; Benafia, Retraint & Brou, 2018 ; Yao et al, 2017 ; Fang et al, 2011 ; Wang & Lu, 2017 ; Tong et al, 2003 ; Wang et al, 2003 ; Lei et al, 2019 ; Lu & Lu, 2004 ). In this study, the influence of surface morphologies on the adhesion, proliferation and differentiation of hBMSCs might be safely excluded, while the samples in the experimental and controlled groups show a similar surface morphology (with surface roughness R a of 1.73 ± 0.11 and 1.82 ± 0.06 μm, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Previous works showed that surface mechanical attrition treatment (SMAT) technology might be applied to solve this problem by improving osseointegration ability on Ti surface (Lai et al, 2012). In addition, SMAT metals have the advantages of high strength (Fang et al, 2011), decreased surface alloying temperature/time due to high diffusion rate (Wang & Lu, 2017) and high chemical reactivity (Tong et al, 2003), and their wear resistance and fatigue resistance are also significantly improved (Wang et al, 2003;Lei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion behavior of nanostructured materials has attracted a lot of studies in recent years, mostly due to its importance in controlling surface alloying and other diffusion-related processes [1][2][3]. For example, the mean diffusivity in nanostructured Fe was detected to be 7-9 orders of magnitude higher than the bulk diffusivity, due to significantly enhanced diffusion along grain boundaries (GBs) produced by severe plastic deformation (SPD) [1,2,4]. This benefited the surface alloying processes (such as nitriding and chromizing) of steels, so that they could be achieved at much lower temperatures relative to the conventional processes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that previous works mostly concentrated on the microstructure and thermal stability of nanostructured samples after isothermal annealing treatments without elemental diffusion [2,[12][13][14], the samples directly after diffusion were seldom studied. As we know, the chemically diffused elements play an important role on the microstructure evolution of base materials by such effects as alloying or GB segregation.…”
Section: Introductionmentioning
confidence: 99%